2021
DOI: 10.3390/cryst11111424
|View full text |Cite
|
Sign up to set email alerts
|

New Low-Dimensional Hybrid Perovskitoids Based on Lead Bromide with Organic Cations from Charge-Transfer Complexes

Abstract: We have obtained a series of low-dimensional hybrid perovskitoids (often referred to as perovskites) based on lead bromide. As organic cations, the derivatives of polyaromatic and conjugated molecules, such as anthracene, pyrene and (E)-stilbene, were chosen to form charge-transfer complexes with various organic acceptors for use as highly tunable components of hybrid perovskite solar cells. X-ray diffraction analysis showed these crystalline materials to be new 1D- and pseudo-layered 0D-perovskitoids with lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
(112 reference statements)
0
1
0
Order By: Relevance
“…Researchers found that the resulting products via the CT interactions possess unique chemical, biological, and physical properties. The CT complexations are significantly beneficial to non-academic fields (pharmacology, material science, engineering, technology, and medicine) in addition to academia (chemistry, physics, biology, and biochemistry) [12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introduction 1backgroundmentioning
confidence: 99%
“…Researchers found that the resulting products via the CT interactions possess unique chemical, biological, and physical properties. The CT complexations are significantly beneficial to non-academic fields (pharmacology, material science, engineering, technology, and medicine) in addition to academia (chemistry, physics, biology, and biochemistry) [12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introduction 1backgroundmentioning
confidence: 99%